2011
DOI: 10.2147/ijn.s19151
|View full text |Cite
|
Sign up to set email alerts
|

Particle size reduction to the nanometer range: a promising approach to improve buccal absorption of poorly water-soluble drugs

Abstract: Poorly water-soluble drugs, such as phenylephrine, offer challenging problems for buccal drug delivery. In order to overcome these problems, particle size reduction (to the nanometer range) and cyclodextrin complexation were investigated for permeability enhancement. The apparent solubility in water and the buccal permeation of the original phenylephrine coarse powder, a phenylephrine–cyclodextrin complex and phenylephrine nanosuspensions were characterized. The particle size and particle surface properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Additionally, we investigated the effect of nanoparticle diameter on in vivo efficacy, as size is often regarded as an important factor in delivery ability to various physiological targets. 23,24 All LNPs formulated in this study had diameters less than 300 nm. For these diameters, no correlation between size and in vivo efficacy was observed at an siRNA dose of 5 mg/kg (Figure 5b) or at lower siRNA doses (< 0.5 mg/kg, data not shown).…”
Section: Resultsmentioning
confidence: 90%
“…Additionally, we investigated the effect of nanoparticle diameter on in vivo efficacy, as size is often regarded as an important factor in delivery ability to various physiological targets. 23,24 All LNPs formulated in this study had diameters less than 300 nm. For these diameters, no correlation between size and in vivo efficacy was observed at an siRNA dose of 5 mg/kg (Figure 5b) or at lower siRNA doses (< 0.5 mg/kg, data not shown).…”
Section: Resultsmentioning
confidence: 90%
“…Several clinical studies have reported the use of ultramicronized PEA (um-PEA) in the treatment of various syndromes associated with chronic pain that are poorly responsive to standard therapies [ 24 26 ]. The ultramicronization process is often used in the preparation of pharmaceuticals, as it yields a crystalline structure with higher energy content and smaller particle size which contributes to better distribution and diffusion and therefore a greater pharmacological efficacy [ 27 , 28 ]. Interestingly, a recent study reported that micronized PEA/um-PEA displayed better oral efficacy compared to nonmicronized PEA in a rat model of inflammatory pain [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The milk distribution study showed that nano-sized lasalocid exhibited faster distribution of the active compound in the milk than microsized lasalocid. This may be the result of nanosized active compound having faster dissolution characteristics, 41 leading to a faster distribution of the active compound throughout the mammary gland. This is consistent with the finding that best tissue distribution rates are expected when the active compound is administered in a formulation with homogeneously distributed particles of small size.…”
Section: Discussionmentioning
confidence: 99%